(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Background: The relationship between diabetes mellitus and periodontal disease remains an overlooked public health concern. In Saudi Arabia, the prevalence of diabetes has risen sharply, now affecting an estimated 4.6 million adults around 21.3% of the population. At the same time, more than 85% of adults are reported to suffer from some form of periodontal disease. Although awareness of the connection between these two conditions is gradually increasing, there is still a lack of thorough research into clinical evidence and patient understanding within the Saudi context. Methods: Following PRISMA 2020 guidelines, we conducted a bibliographic search of PubMed/MEDLINE, Scopus, Web of Science, and Google Scholar from January 2000 to July 2025. The criteria involved studies with a Saudi population of all ages who had a clinical assessment of periodontitis and had their diabetes status documented. The screening, data extraction, and risk of bias assessment were carried out by two independent reviewers. Owing to methodological diversity, we undertook a narrative synthesis. Results: Twelve studies met inclusion criteria, comprising 4739 participants. Among the adult population, the uncontrolled diabetes mellitus (defining it if the associated HbA1c >6.5%) was associated with periodontitis (OR: 2.779, 95% CI: 1.425-5.419, p=0.003) and periodontitis had a significantly higher periodontitis risk. There were significant diabetes-hypertension comorbidity and radiographic bone loss (p=0.004) relationships. The T1DM pediatric population had a greater prevalence of gingivitis (p<0.05) and oral health-related quality of life impacts (P=0.003) than other populations. The results of the awareness assessment showed that the respondents had considerable knowledge gaps because only 21.8% of the diabetic patients were aware of the two-way relationships of gum disease and glucose control. Conclusions: The findings of this systematic review provide strong clinical proof of the association between diabetes and periodontal disease for the Saudi populations. The periodontitis risk for uncontrolled diabetes was found to be 2.78-fold higher, thus reinforcing gaps in critical diabetes patient awareness. This indicates that there is an undue burden of risk for optimum control of disease management strategies. There is an immediate need for more optimum integrated health care strategies, improved patient education on changes in behavior, and more diabetes research focusing on standardized glycemic control definitions in the context of Saudi Arabia.